THE ROLE OF INNOVATION IN MEDIATING THE EFFECTS OF MARKET ORIENTATION AND ENTREPRENEURIAL ORIENTATION ON BUSINESS PERFORMANCE IN THE CONTEXT OF SMES - Widhy Tri Astuti; Achmad Sudiro; Djumilah Hadiwidjojo; Sudjatno (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
The aims of this study are to examine and analyse the role of innovation in mediating the effect of market orientation and entrepreneurial orientation on business performance in the context of small and medium size enterprises (SMEs). The results showed that market orientation and entrepreneurial orientation proved to have a positive and significant effect on business performance. An interesting result of this study is that that innovation plays a role as a mediator in the influence of market orientation and entrepreneurial orientation on business performance in the context of SMEs. Nevertheless, the mediating role of innovation in determining the magnitude of the influence between market orientation and entrepreneurial orientation on business performance is smaller than the direct influence. Overall, the results of this study indicate that a combination of market orientation and entrepreneurial orientation are the instruments that underlie SMEs in shaping innovation so as to improve business performance in the context of SMEs.